Flexural response of reinforced concrete beams withh embedded CFRP plates - Ohu, Rachael Bukola (2012)
Fiber reinforced polymers (FRP) are used as either internal or as external reinforcements in structures. However, issues related to reduced ductility performance and large deflections have been observed by several other researchers which needs to be addressed in order for these reinforcements to be more widely adopted as alternative structural reinforcements in practice. In this regard, an alternative method of using FRP plates as internal reinforcements in concrete beams is explored and presented in this thesis in terms of ductility/ deformability performance as well as other structural responses under static loading with the aim of improving the ductility/deformability response as well as examining some aspects of structural behaviour. In addition, the bond behaviour of this reinforcement which is a key factor towards the improvement of structural performance especially with regards to the bond-slip behaviour at service and ultimate conditions was studied. Thus, different surface treatments have been experimentally investigated through pullout tests to identify the best bond effects. Based on the experimental bondslip behaviour obtained, a concrete – CFRP plate bond interface model is proposed and incorporated into a finite element algorithm for the analysis of concrete beams reinforced with embedded CFRP plates taking into consideration differences in the surface textures of the embedded CFRP plate. A 2-D nonlinear finite element program was thus adopted for the analysis of the proposed reinforcement technique. The most suitable surface treatment obtained from the pullout tests was then adopted in the embedded carbon fiber reinforced polymer plates (CFRP) in concrete beams via experimental testing under flexural load. The results showed that embedded CFRP plates in concrete beams is an effective alternative form of reinforcement with a 37% decrease in deflection response and a 54% improvement in deformation/ductility performance. In addition the bond behaviour is dependent on the type of surface treatment with an increase in bond strength ranging between 78% - 284%. While an increase in concrete strength led to a 58% increase in the bond strength of embedded CFRP plates in concrete. Similarly, the proposed bond model for the embedded CFRP plates successfully depicted the concrete-CFRP plate interface behaviour and the FE results were in agreement with the experimental results with a percentage difference of 12% exhibiting a realistic simulation of the experimental load-deflection response.